Factors Affecting Publication Impact and Citation Trends Over Time - De Groote, Sandra L.; Scoulas, Jung Mi; Dempsey, Paula R.; Barrett, Felicia (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – The researchers investigated whether faculty use of the references in articles had a relationship with the later impact of the publication (measured by citation counts). The paper also reported on additional factors that may influence the later impact of publications.Methods – This researchers analyzed data for articles published by faculty at a large public university from 1995 to 2015. Data were obtained from the Scopus abstract and citation database and analyzed using SPSS27 to conduct Pearson’s correlations and regression analysis.Results – The number of references included in publications and the number of citations articles received each year following publication have increased over time. Publications received a greater number of citations annually in their 6th to 10th years, compared to the first 5. The number of references included in an article had a weak correlation with the number of citations an article received. Grant funded articles included more references and later received more citations than non-grant funded articles. Several variables, including number of references used in an article, the number of co-authors, and whether the article was grant funded, were shown to correlate with the later impact of a publication.Conclusion – Based on the results, researchers should seek out grant funding and generously incorporate literature into their co-authored publications to increase their publications' potential for future impact. These factors may influence article quality, resulting in more citations over time. Further research is needed to better understand their influence and the influence of other factors.